Sistem Informasi Pemesanan Menu Makanan dan Minuman pada Kafe Lori Berbasis Web - Malik Fajar Siddiq; Murti Retnowo (STMIK Budi Darma, 2023)
A cafe is a place that serves drinks and culinary orders. A cafe is also a center of social interaction where people can gather, talk, joke around, or just fill their free time. Ordering is an activity carried out by consumers before purchasing. To achieve customer satisfaction, the company must have a good ordering system. The research method used in this research uses data collection methods, namely observation, interviews and literature study. Currently Lori Cafe is experiencing difficulties in serving orders and is still using records that are not yet computerized or still using a conventional system. Where buyers have to wait too long to order culinary delights, apart from that, waiters also have difficulty recording orders manually using paper. Manually recording orders is less efficient in terms of time. So, to realize consumer satisfaction in culinary orders, a web-based food ordering information system was designed using the Html, CSS, PHP programming language and here I use a database, namely Mysql.